Hubungan tingkat pengetahuan dan sikap dengan keikutsertaan dalam Posyandu Lansia - Restia Cahyaningrum; Siti Tyastuti; Sabar Santoso (Poltekkes Kemenkes Yogyakarta, 2012)
United State Census (based on the BPS rate Indonesia) Indonesia experienced a trend of rising population aged above 65 years old. Of the elderly population distribution according to the provinces, the percentage of elderly residents in the province of Yogyakarta special region of 14.02%, 10.99% Central Java, East Java and Bali 1A,92% 6.95%. The number of pain (morbidity) of elderly increases, 28% in 2003, 29.9% in 2005, 19.3% in 2007, and 301% in 2009. Quality improvement in terms of biological and psychosocial needs so that they can enjoy a better life, and support preventive action, as well as promotive health in Primary Health Care according to the paradigm of healthy. One effort that can be done is with a program of Posyandu for elderly. Posyandu for elderly (Age Group) is a health service place for the elderly in the community where the process of the establishment and their implementation is carried out by the community with non-governmental organizations Government and cross-sector nongovernment, private, charitable organizations and others, in a series of efforts aimed at servicing and preventive promotive. ln the activities of the knowledge and attitude about posyandu for elderly is very influential to the liveliness of the posyandu presence. The purpose of this research is to determine the correlations of the level of knowledge and attitude of elderly with posyandu for elderly participation. This type of research using the method of research studies the correlation (Correlation Study) and the design is observational/survey. The samples in the study totaled 67 elderly in Posyandu for elderly RW 4 Wards of Wirogunan. The instruments used for data collection in this study is a questionnaire and secondary data or documentation. Multivariate data analysis using logistic regression test. the result is PR value relationship level of knowledge and attitudes of elderly with participation in Posyandu for elderly through Logistic regression showed the 3.252 for the level of knowledge ta 2.990 for attitudes